Cutaneous toxicities associated with vemurafenib therapy in 107 patients with BRAF V600E mutation‐positive metastatic melanoma, including recognition and management of rare presentations. (11th October 2015) - Sinha, R.; Larkin, J.; Gore, M.; Fearfield, L.
Summary: Background: Vemurafenib significantly improved overall survival compared with dacarbazine in patients with metastatic or unresectable BRAF V600E‐positive melanoma in the BRIM‐3 trial. However, vemurafenib was associated with a number of skin‐related adverse events (AEs). Objectives: To investigate the incidence and management of vemurafenib‐associated skin AEs. Methods: This retrospective, observational study included adult patients with stage IIIC or IV melanoma who received vemurafenib between March 2010 and August 2013. Patients received oral vemurafenib 960 mg twice daily, with dose interruptions and reductions allowed for AE management. Results: In total 107 patients were treated with vemurafenib during the study period. The most frequent clinically important skin‐related AEs were rash (64%), squamoproliferative growths (41%), photosensitivity (40%) and squamous cell carcinoma (SCC) or keratoacanthoma (KA; 20%). Rare cases of granulomatous dermatitis and cutaneous T‐cell lymphoma were also found. Rash was manageable with corticosteroids and dose modifications; squamoproliferative growths and SCCs/KAs were treated with cryotherapy and surgical excision, respectively. Patients were counselled regarding phototoxicity. The uncontrolled nature and retrospective design of the study, and the small patient numbers are limitations. Conclusions: Vemurafenib appears to have a predictable and manageable AE profile. Proactive management can limit the impact of AEs on patients, allowing treatment to continue despite toxicities. Abstract : What's already known about this topic? Vemurafenib is associated with a number of cutaneous side‐effects. What does this study add? This article provides additional evidence of the toxicity profile of vemurafenib and consolidates what is known from safety trials. Linked Comment: Walsh, Br J Dermatol 2015; 173: 892–893 .